Uma caracterização de projetos de software open source do ponto de vista de atributos de qualidade de produto - SILVA, Antonio César Brandão Gomes da (2017)
Context: Several Open Source Software (OSS) projects have adopted frequent releases as a strategy to deliver both new features and fix bugs on time. The need to accelerate software delivery, supporting faster time-to-market and frequent community developers/users feedback are issues that have lead to relevant changes in software development practices. In this way, each OSS project has its own priorities established by its respective communities. Goal: Identify the main characteristics of software release initiatives in OSS projects, the motivations behind their adoption, strategies applied, as well as advantages and difficulties found. Besides that search for evidence that clarify the relationships between target attributes, priorities assigned to the registered issues and the ways they are delivered by product releases. Method: In the first step of this work it was conducted a Systematic Literature Review (SLR) to reach one of the goals. In the second step an exploratory study was planned to identify quality attributes through the data analysis of repositories of three well-known OSS projects: Libre Office, Eclipse and Mozilla Firefox.Results: The SLR includes 30 publications from January 2006 to July 2016 and reveals nine advantages that characterize software release approaches in OSS projects; four challenge issues; three possibilities of implementation and two main motivations towards the adoption of RR; and finally four main strategies to implement it. the exploratory study verified that evidence provided by the participants suggest that OSS community developers use criteria/priorities driven by specific software product quality attributes to plan and perform software releases. Conclusion: This work provides an up-to-date and structured understanding of the software release approaches in the context of OSS projects based on findings systematically collected from a list of relevant references in the last decade. And finally an indication that the prioritization of quality attributes in projects tend to consider the profile of each project